Objectivity : the obligations of impersonal reason - Rescher, Nicholas (Notre Dame, Ind. : University of Notre Dame Press, 1997)
Nicholas Rescher presents an original pragmatic defense of the issue of objectivity. Rescher employs reasoned argumentation in restoring objectivity to its place of prominence and utility within social and philosophical discourse. By tracing the source of objectivity back to the very core of rationality itself, Rescher locates objectivity's reason for being deep in our nature as rational animals. His project rehabilitates the case for objectivity by subjecting relativistic and negativistic thinking to close critical scrutiny, revealing the flaws and fallacies at work in the deliberations of those who dismiss objectivity as obsolete and untenable. Rescher takes to task the cultural relativism of contemporary social science and social theory, as well as that of liberalistic political correctness and the postmodern aversion to the normative. In holding such relativistic thinking up to the light of rational argument, he demonstrates that a rejection of objectivity is in fact unreasonable. Rescher further reveals that a relativistic apathy to truth and rightness actually destroys, in effect, the very conception it presumably elucidates.
Objectivity and rationality -- Critics of objectivity -- Objectivity and consensus -- Against cognitive relativism -- Objectivity and quantification -- Objectivity and communication -- Ontological objectivity grounds cognitive objectivity -- The pragmatic rationale of cognitive objectivity -- Moral objectivity : against moral relativism -- Moral objectivity : the rationality and universality of moral principles -- Value objectivity -- Hermeneutic objectivity : against deconstructionism -- Conclusion : Is objectivity subject to limits?
Includes bibliographical references (p. 215-227) and index.
Keywords: Objectivity